Case report: A Chinese boy with facial dysmorphism, immunodeficiency, livedo, and short stature syndrome - Jiang, Lihong; Chen, Xin; Zheng, Jiaqi; Wang, Meilin; Bo, Hui; Liu, Geli (Frontiers in Pediatrics, 2022)
Facial dysmorphism, immunodeficiency, livedo, and short stature (FILS)syndrome is a rare autosomal recessive disease. In this case study, we reported on the first known case of FILS syndrome in a Chinese boy. The patient had short stature and suffered from recurrent respiratory infections up to the age of 4 years. Other symptoms of the disease included livedo on the inner side of upper limbs and thigh skin, prominent forehead, low anterior and posterior hairline, short and downward sloping eyelid fissure, low ear position, long nasal tip and columella, and a small mouth with irregular teeth. A whole exon gene sequencing was performed and revealed two mutations within the polymerase ε 1 (POLE1) gene. One of the mutations was a splicing mutation (c.5811+2T> C) derived from the mother, while the other was a nonsense mutation (c.2006G>A) derived from the father. These two mutation sites were not reported in previous FILS syndrome cases. The DNA polymerase ε is involved in the DNA replication within eukaryotic cells, while the 3'-5’ exonuclease activity can reduce DNA replication errors. Therefore, mutations in POLE1 could possibly increase the risk of developing tumors in children.